The Decline and Fall of Human Fertility - John Aitken (Fertility & Reproduction, 2023)
Over the last half century, the world has seen a steep decline in fertility in virtually every country on Earth, with the result that most advanced industrialized societies now have fertility rates that are well below replacement levels (conventionally set at 2.1 children per woman). This decline in fertility has been particularly marked in the Tiger economies of Southeast Asia but is essentially ubiquitous, even in populous nations such as India and China. These trends mean that, in the short term, advanced industrialized nations such as Australia can only prop up their ageing, flagging populations by encouraging record levels of immigration. Ultimately, however, we need to address this issue by addressing the causes of global fertility decline, not its consequences. This decline is being driven by increasing prosperity through the mediation of a range of social factors, the most powerful of which is the education of women and an accompanying shift in life’s purpose away from procreation. In addition, environmental and lifestyle factors are also having a profound impact on our fecundity, particularly in the male where increasing prosperity is associated with an exponential rise in the incidence of testicular cancer and a secular decline on semen quality and testosterone levels. On a different time scale, we should also recognize that the reduced fertility rates associated with the demographic transition are lessening selection pressure on high fecundity genotypes. The retention of poor reproductive genes within the human population is also being exacerbated by the increased uptake of assisted conception therapy. If we continue to rely on the latter to solve all of infertility’s woes, the growth of the ART industry may ultimately reach a scale where it serves to reduce human fertility still further, leading our species into an infertility trap.